Analyzing Make-Up Artist Promotion Strategy on Social Media Instagram in Surakarta City - Ramadhan, Muhammad Gilang; Shabrina, Winda; Setyawan, Sidiq (Jogjakarta Communication Conference (JCC), 2023)
In this digital era, people have the potential to become cosmetic and make-up users as part of daily life, so the cosmetic market share is very large. Displayed on Instagram to get the attention of others in the form of "likes" and "compliments" as much as possible, part of narcissism in social media that can increase the endorphins of happiness, but not everyone is talented at dressing themselves, so they call the services of MUA to beautify their appearance. This study uses a qualitative research method with a depth interview and purposive sampling technique. In this study, the results of observations are concluded as an elaboration of promotion strategy that must be carried out by beginner MUA who have started a business but want to attract consumers of makeup services with knowing promotion strategy using social media Instagram to built promotion strategy. The research result obtained three of MUA which is researched when examined from AIDA theory is a form of effect that explains how the audience is able to digest a promotion communication strategy message to make it take an attitude and behave like what the communicator expects.